2004
DOI: 10.1099/vir.0.80135-0
|View full text |Cite
|
Sign up to set email alerts
|

The glycoprotein of a fish rhabdovirus profiles the virus-specific T-cell repertoire in rainbow trout

Abstract: T-cell responses to viruses are still poorly investigated in lower vertebrates. In rainbow trout, a specific clonal expansion of T cells in response to infection with viral haemorrhagic septicaemia virus (VHSV) was recently identified. Expanded T-cell clones expressed a unique 8 aa Vb4-Jb1 junction (SSGDSYSE) in different individuals, reminiscent of a typical public response. To get further insight into the nature of this response the modifications of the T-cell repertoire following immunization with plasmid e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 50 publications
(55 reference statements)
2
27
1
Order By: Relevance
“…The importance of the G protein in VHSV virulence has been subjected to a lot of research, motivated partly by the fact that the G protein is involved in virus attachment and entry (25). However, it has not been possible to link particular residues or motifs of the G protein to virulence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of the G protein in VHSV virulence has been subjected to a lot of research, motivated partly by the fact that the G protein is involved in virus attachment and entry (25). However, it has not been possible to link particular residues or motifs of the G protein to virulence.…”
Section: Discussionmentioning
confidence: 99%
“…For the NV ORF, we also introduced a three-amino-acid en-block mutation, VSE to ILD (positions 55 to 57). The candidate proteins (G, NV, and L) were chosen because the G protein is a membrane protein involved in virus attachment and entry (25) and the NV protein has been shown to have an impact on antiapoptosis functions and virulence (23). There are very few, if any, studies addressing to what extent the polymerase plays a role in the virulence of novirhabdoviruses, but it is well known that a single amino acid mutation in PB2 (polymerase B2 protein) of human influenza virus renders the virus able to replicate in chicken cells (26).…”
Section: Resultsmentioning
confidence: 99%
“…Viral G protein can interact with cell-surface receptors to mediate not only virus entry, but also the host immune system activation (Verjan et al, 2008), and N protein plays a critical role in the encapsidation and replication of viral genomic RNA (Green et al, 2006). Previous reports of DNA vaccination with VHSV G gene have shown that injected plasmids could be taken up by muscle cells at the site of injection and the viral G protein is expressed on the surface of myocytes, hereby interacting with the surface cell receptors to activate the immune system of the fish (Boudinot et al, 2004;Lorenzen et al, 2005Lorenzen et al, , 2009. It is likely that plasmid DNA containing SCRV G gene functions in a similar way to activate the immune system of the mandarin fish, thus protecting the fish from virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing data previously available for the G protein of both isolates of VHSV used here identified 2 nt substitutions leading to a single aa substitution (Ser113Gly position; 0.2%); this finding was further verified in the present study, both from infected cells and harvested tissue. The G protein is responsible for host cellular entry of the virus by means of receptormediated endocytosis, is the target molecule for neutralizing antibodies (Boudinot et al 2004), and has already been demonstrated to play a decisive role in determining the virulence of VHSV (Béarzotti et al 1995. The position of this mutation proved interesting.…”
Section: Discussionmentioning
confidence: 99%